The remote work of the high school teacher linked to the regional education center of Ponta Grossa during the pandemic of the novel Coronavirus - de Mello , Édina Maria Machado; da Silva , Lenir Aparecida Mainardes (Seven Editora, 2023)
This article consists of an analysis of the remote work of high school teachers, linked to the Regional Education Center of the city of Ponta Grossa, State of Paraná, Brazil, in the context of the coronavirus (COVID-19) pandemic, with a view to identifying the possible occurrence of existential damage as a result of the violation of the right to disconnection. Lo and behold, one of the first sanitary measures implemented by the authorities to contain the spread of the COVID-19 virus was the suspension of face-to-face school activities, and with the prolongation of such measures, in the face of the rampant increase in the number of cases of the disease, it was decided to establish a new model for the continuity of classes and compliance with the school calendar, making use of virtual resources that allowed the teaching of remote classes. This reality had significant effects on the work routine and on the private lives of these professionals who, suddenly, were compelled to adapt to this new format of work, carried out from within their homes, using their own resources. There were several transformations and difficulties resulting from this new way of working, notably in relation to time and intensification of work, shortening of rest periods, damage to social, family and professional relationships, as well as several other mishaps felt and reported by professionals, through this research, conducted through a questionnaire made available through a virtual tool. The data obtained with the research pointed to the existence of elements that can characterize the existential damage, as well as well-founded indications that the work in such conditions is capable of causing the worker existential damage, by violating the right to disconnection. DOI:https://doi.org/10.56238/emerrelcovid19-049